Pengaruh Thin Capitalization, Transfer Pricing, dan Manajemen Laba Terhadap Agresivitas Pajak - Trisnawati, Fransiska Desy; Ardillah, Kenny (UNIVERSITAS KALBIS, 2023)
The effect of thin capitalization, transfer pricing, and earnings management towards tax aggressiveness. The purpose of this research is to determine the effect of thin capitalization, transfer pricing, and earning management on tax aggressiveness. The population in this study are all manufacturing companies in the consumer goods sector listed on the Indonesia Stock Exchange in 2016-2020. The number of research samples obtained by 39 companies using purposive sampling technique, in order to obtain 195 observational data. This research uses multiple linear regression method. The research results show that thin capitalization has a positive effect on tax aggressiveness. Transfer pricing and earnings management have no effect on tax aggressiveness.